"On the Dot"—The Timing of Self‐Assembled Growth to the Quantum Scale. Issue 34 (15th March 2017) - Sonkaria, Sanjiv; Ahn, Sung‐Hoon; Lee, Caroline S.; Khare, Varsha
Abstract: Understanding the complex world of material growth and tunability has mystified the minds of material scientists and has been met with increasing efforts to close the gap between controllability and applicability. The reality of this journey is frustratingly tortuous but is being eased through better conceptual appreciation of metal crystalline frameworks that originate from shape and size dependent solvent responsive growth patterns. The quantum confinement of TiO2 in the range of 0.8–2 nm has been synthetically challenging to achieve but lessons from biomineralization processes have enabled alternative routes to be explored via self‐induced pre‐nucleation events. In driving this concept, we have incorporated many of these key features integrating aspects of low temperature annealing at the interface of complex heterogeneous nucleation between hard and soft materials to arrest the biomimetic amorphous phase of TiO2 to a tunable crystalline quantumized state. The stabilization of metastable states of quantum sized TiO2 driven by kinetic and thermodynamic processes show hallmarks of biomineralized controlled events that suggest the inter‐play between new pathways and interfacial energies that preferentially favor low dimensionality at the quantum scale. This provides the potential to re‐direct synthetic assemblies under tightly controlled parameters to generate a host of new materials with size, shape and anisotropic properties as smart stimuli responsive materials. These new stabilities leading to the growth arrest of TiO2 are discussed in terms of molecular interactions and structural frameworks that were previously inaccessible via conventional routes. There exists an undiscovered parallel between synthetic and biomineralized routes enabling unprecedented access to the availability and tunability of novel quantum confined materials. The parametrics of complex material design at the crossroads of synthetically and biologically driven processes is only now surfacing. Abstract : Case in question : Accessibility to new synthetic materials to sub‐nanometer levels to quantum scales is not trivial, in this case it is TiO2 . The evolution of some biominerals with equilibrium morphologies stabilized by ligand compartmentalization enabling control over shape and size reveals mechanistic clues to engineer biomimetic approaches. This establishes a new route to material tunability and accessibility to quantum sub‐bands that show a profound interdependence on anisotropic growth patterns.